Pemanfaatan Penggunaan Twitter terhadap Kemampuan Literasi Informasi Mahasiswa Prodi Perpustakaan dan Ilmu Informasi UNP 2020 - Adrian, Nicky; Ardoni, Ardoni (YASIN, 2024)
Social media is a very popular information dissemination platform, with one in three people worldwide and two-thirds of internet users using social media. There are many ways to obtain the required information, one of which is by accessing the social media platform Twitter. In order to obtain information effectively and efficiently, students need a skill in processing information, which is information literacy. For students, information literacy skills will help them in finding and obtaining information critically and not being deceived by information whose accuracy is uncertain. This study aims to explore the use of the social media platform Twitter and its impact on the information literacy skills of students in the Library and Information Science Program at Universitas Negeri Padang in 2020. The research method used a qualitative approach with interview techniques as the data collection instrument. The results of the data analysis can be concluded that Twitter plays a significant role in improving information literacy among students. The majority of respondents use Twitter for various purposes, ranging from finding the latest information, verifying the validity of information, to sharing personal experiences. Most students use this platform as a source of up-to-date information, but there are also those who actively join specific accounts focused on literacy and learning. Thus, Twitter is considered an effective means of improving information literacy skills among students.